Answer:
Explanation:
Choose the right statement is true about the equation (x – 4)(x + 2) = 16
A. The equation x – 4 = 16 can be used to solve for a solution of the given equation.
we have x - 4 = 16 or x = 4+ 16, x = 20
we replace x = 20 into (x – 4)(x + 2) = 16
then we have (20-4)(20+2) = 16, but it is wrong.
B. The standard form of the equation is x2 – 2x – 8 = 0.
we developp: (x – 4)(x + 2) = 16
x^2 -4x + 2x -8 = 16
or x^2 -2x -24 =0
So this statement is wrong.
C. The factored form of the equation is (x + 4)(x – 6) = 0.
we developp: (x + 4)(x – 6) = 0
we have x^2 - 6x +4x -24 =0
or x^2 -2x -24=0
That statement is right.
D. One solution of the equation is x = –6.
we replace x = -6 into (x – 4)(x + 2) = 16
and we have ( -6 - 4)( -6 +2) =16
or -10* (-4) =16
or 40 = 16, wrong
The answer is C